Pengaruh Work Life Balance, Stres Kerja Dan Pengembangan Karir Terhadap Retensi Karyawan Dengan Job Engagement Sebagai Variabel Intervening Pada PT. Tidar Kerinci Agung - Tomy Irwandi; M. Afuan; Yamasitha Yamasitha (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of work-life balance, work stress, and career development on employee retention, with job engagement serving as an intervening variable, at PT. Tidar Kerinci Agung. The study employs a Structural Equation Modeling (SEM) approach using SmartPLS 3.0 software for analysis. The population and sample for this study consist of employees from PT. Tidar Kerinci Agung. The results indicate a significant influence of work-life balance on job engagement and a significant influence of work stress on job engagement. However, career development was found to have no significant influence on job engagement. Regarding employee retention, work-life balance and career development showed no significant influence, whereas work stress had a significant influence. Job engagement was found to have a significant influence on employee retention. Furthermore, job engagement was found to mediate the relationship of work-life balance and work stress with employee retention, but it did not mediate the relationship between career development and employee retention.